Simulation of Irregular Waves in a Numerical Wave Tank - Zhi-Fu, L.; YuYun, S.; HuiLonga, R.; Hui, L.; Ashraf, M.A. (De Gruyter Open, 2015)
The time domain boundary element method was utilized to simulate the propagation of the irregular waves in a numerical wave tank. The problem was solved in a time-marching scheme, upon the irregular waves being fed through the inflow boundary, in which the theoretical solution was obtained from the wave energy spectrum. The open boundary condition was modeled by the multi transmitting formula (MTF), in which the phase velocity was calculated according to the Sommerfeld's condition. The velocity potential and wave elevation were directly obtained by integrating the free surface condition twice, with respect to time. The accuracy of the developed numerical scheme was verified by simulating the propagation of irregular waves. The numerical results show good agreements with the analytical solutions, which prove that the proposed scheme is a promising way to the simulation of wave-body interactions.